Rancang Bangun Galeri UMKM Britama Berbasis E-Commerce - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Rodianto Rodianto; Mega Tazayyun (STMIK Budi Darma, 2022)
UMKM BRItama in Batudulang Village is a small and medium micro enterprise that is engaged in the creative economy by marketing the products of Batudulang Village. UMKM BRItama in Batudulang Village in the process of product marketing applies the conventional transaction because there is no special media that is used as a marketing solution. Based on this, we need an online media in the form of a website that can be accessed by all internet users without space and time limits. This study uses a descriptive qualitative approach with a software development methodology using Waterfall. The system design process with a structured approach and the construction stage using the Codeigniter framework. Before being implemented, this application will be tested by two parties, namely the first from the researcher as a developer and a competent party in software engineering to find out that the functions made are already running according to the specified specifications. The two tests were carried out by BRItama UMKM managers and several customers to ensure that the applications made were in accordance with their needs. To ensure the suitability of the user's needs of the application made testing using the black-box testing method. Of all the testing processes, 99% stated that the functions were running according to specifications and applications that had been made according to needs. UMKM BRItama Batudulang Village has become an application as a medium in product marketing without boundaries of space and time and helps expand the scope of product marketing